A critical discussion of industrial heritage buildings adaptive re-use as film spaces, case study: industrial heritage buildings at Istanbul. Issue 3 (1st September 2020) - Babutsalı Alpler, Zehra; Şahin, Nil Paşaoğluları; Dağlı, Uğur Ulaş
ABSTRACT: Adaptive reuse has been successfully applied in many types of facilities. It is possible to see examples of culturally significant industrial buildings' adaptive reuse. Altering adaptations as film spaces has become a fascinating debate recently. The aim of this study is to investigate efficiency of adapting industrial heritage buildings as film spaces on the long-term conservation and sustainable future of these buildings. Three industrial buildings that have been adaptively reused as film spaces in İstanbul, Turkey (soap-factory, warehouse for carbonated water and listed building at Beykoz Leather and Shoe Factory) are cases of this study. This study concludes that cultural significance is retained due to minimal changes observed on the external characteristics. Their reuse as film spaces has enriched the physical, locational/environmental and social/cultural performance of industrial heritage buildings. Two different approaches as temporary and permanent have been investigated. This study concludes that adapting industrial heritage buildings as film spaces is an appropriate decision, especially when it is adopted permanently with holistic/comprehensive approach from the beginning of adaptation process as creative hub of production. Results suggest that this approach has brought diverse additional impacts, both to conservation of these significant buildings and to their locations' social, physical and economic well-being.